2018
DOI: 10.1212/wnl.0000000000006037
|View full text |Cite
|
Sign up to set email alerts
|

Determinants and outcome of multiple and early recurrent cervical artery dissections

Abstract: Patients with multiple and early recurrent CeAD share similar risk factors, clinical characteristics, and functional outcome. Compared to patients with single nonrecurrent CeAD, they are more likely to have recurrent cerebral ischemia at 3 to 6 months, possibly reflecting an underlying transient vasculopathy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
46
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(48 citation statements)
references
References 41 publications
2
46
0
Order By: Relevance
“…Although multiple dissections were more often associated with risk factors or predisposing activities, the CADISP study showed no effect on 3-month functional outcome measured by modified Rankin Scale score. Results from a multicenter study evaluating multiple and early recurrent CeAD by the CADISP group in 2018 revealed no difference in functional outcomes but a higher incidence of cerebral ischemia at 3 to 6 months compared with single nonrecurrent CeAD patients [18]. The CADISP group also analyzed a subcohort of 690 CeAD and 556 non-CEAD ischemic stroke patients [19].…”
Section: Discussionmentioning
confidence: 99%
“…Although multiple dissections were more often associated with risk factors or predisposing activities, the CADISP study showed no effect on 3-month functional outcome measured by modified Rankin Scale score. Results from a multicenter study evaluating multiple and early recurrent CeAD by the CADISP group in 2018 revealed no difference in functional outcomes but a higher incidence of cerebral ischemia at 3 to 6 months compared with single nonrecurrent CeAD patients [18]. The CADISP group also analyzed a subcohort of 690 CeAD and 556 non-CEAD ischemic stroke patients [19].…”
Section: Discussionmentioning
confidence: 99%
“…56 Interestingly, MWA has been associated with atrial fibrillation and patent foramen ovale (PFO) -2 conditions associated with emboli. 61 There are a few published cases of cervical artery dissection in association with triptan use, but a causality link has not been demonstrated,the association may be with migraine and not with triptan use. 59,60 Migraine is not known to predispose to recurrence.…”
Section: Expert Commentarymentioning
confidence: 99%
“…59,60 Migraine is not known to predispose to recurrence. 61 There are a few published cases of cervical artery dissection in association with triptan use, but a causality link has not been demonstrated,the association may be with migraine and not with triptan use. 62 Returning to our theoretical patient in Case 2, we can assume that the stroke had an identifiable cause unrelated to triptan use and that using eletriptan is very unlikely to increase the risk of another stroke.…”
mentioning
confidence: 99%
“…In most hospital-based series, 60%-80% of CeAD patients had stroke [4][5][6]. Most patients have a single CeAD during their life, but 10%-15% of the patients present with multiple dissections in different cervical arteries during the acute phase or with new dissection shortly after the first event [6,7], which suggests the existence of a transient vulnerable phase with increased risk of CeAD [8,9]. Although cohorts of patients with recurrent CeAD have been relatively small so far, few recurrent dissections were observed to cause stroke [8,9].…”
Section: Introductionmentioning
confidence: 99%